Developing Islamic Religious Education Curriculum Integrating Religious Moderation and Digital Literacy in the Post-Truth Era - Dwi Rangga Vischa Dewayanie; Septyana Tentiasih (JIIS - Journal of Interdisciplinary Islamic Studies, 2026)
This study aims to analyze the integration of religious moderation and digital literacy into the Islamic Religious Education (IRE) curriculum in the post-truth era and to formulate a conceptual curriculum model relevant to contemporary socio-digital challenges. The study employed a qualitative conceptual research design using a library research approach. Data were collected from books, scientific journal articles, policy documents, and previous studies related to Islamic education, religious moderation, digital literacy, and curriculum development. The data were analyzed using descriptive qualitative content analysis through identification, classification, interpretation, and synthesis of relevant literature. The findings reveal that integrating religious moderation values such as tolerance, justice, balance, and non-violence into the IRE curriculum can foster inclusive, peaceful, and socially responsible learners. In addition, strengthening digital literacy helps students critically evaluate online religious information, prevent misinformation, and engage ethically in digital spaces. The study also found that adaptive learning strategies such as collaborative learning, reflective discussion, and problem-based learning support the implementation of a moderation- and digital literacy-based curriculum. However, challenges related to teachers’ digital competence and unequal technological infrastructure remain significant obstacles. Overall, this study concludes that the integration of religious moderation and digital literacy provides a relevant and transformative framework for developing Islamic Religious Education that is critical, moderate, and adaptive to the challenges of the post-truth era